Tasawuf Falsafi Dan Implikasinya Dalam Pendidikan Islam - Muhammad Anas Ma`arif (VICRATINA, 2018)
The importance of knowing in depth philosophy of Sufi in order to avoid misunderstanding in learning or even practicing the teachings. The philosophical philosophy in view by some Sunni musicologists as a bad teaching for the layman. Some cases like Al-Hallaj were the victims of the government at the time. Or in the context of Indonesia such as the teachings of Siti Jenar with "manunggaling kawulo gusti". The teachings of philosophical Sufism are so profound that the layman can not understand them. The philosophical mysticism itself has significant implications for Islamic education. it can be seen from the goal of Islamic education is to form a human we Kamil. kaffah and perfect. Purpose-This study aims to describe the implications of philosophical Sufism with Islamic education. Design / methodology / approach-This research uses a qualitative approach research with the type of research library that collects data from books, journals and research results related to the theme. Findings - the implications of this research is that educators can internalize the educational model with the character of philosophical Sufism which aims to form our human kamil. Originality - philosophical mysticism can be a concept of education aimed at shaping kaffah and kamil human beings.